557. Impact of Concomitant Hydroxychloroquine Use on Safety and Efficacy of Remdesivir in Moderate COVID-19 Patients. (31st December 2020) - Arribas, Jose Ramon; Arribas, Jose Ramon; Sanyal, Arun J; Soriano, Alex; Chin, Bum Sik; Chin, Bum Sik; Kalimuddin, Shirin; Schreiber, Stefan; Elboudwarej, Emon; Tian, Yuan; Hyland, Robert H; SenGupta, Devi; et al.
Abstract: Background: Remdesivir (RDV) has been shown to shorten recovery time and was well tolerated in patients with severe COVID-19. Hydroxychloroquine (HQN) is an experimental treatment for COVID-19. Effects of coadministration of HQN with RDV have not been studied and are relevant given the long half-life ( 22 days) of HQN. We report the impact of concomitant HQN and RDV use on clinical outcomes and safety in patients with moderate COVID-19. Methods: We enrolled hospitalized patients with confirmed SARS-CoV-2 infection, oxygen saturation >94% on room air, and radiological evidence of pneumonia. Patients were randomized 1:1:1 to receive 5d or 10d of intravenous RDV once daily plus standard of care (SoC), or SoC only. We compared patients on concomitant HQN (HQN pos ) vs not (HQN neg ). Clinical recovery was evaluated using Cox proportional hazards. Covariate adjustment included age, sex, race, region, symptom duration, oxygen support status and obesity. Recovery and adverse events (AEs) were assessed through death, discharge, or d14. Results: Of 584 patients, 199 (34%) received HQN (5d RDV: n=57 [30%]; 10d RDV, n=49 [25%]; SoC: n=93 [47%]). Through median follow-up of 13d (range 1-41d), HQN pos patients on 5d or 10d RDV had a lower recovery rate (adjusted HR [95% CI] 0.78 [0.59, 1.03], p=0.09) with longer median time to recovery (8 vs 6 days) compared to HQN neg . HQN pos compared to HQN neg patients in 5d RDV showed a trend of reduced recovery rate (HR: 0.69 [0.45, 1.04], p=0.080); such an effect was not observed in 10d RDV or SoC (Table 1). More HQN pos than HQN neg patients had AEs in RDV (5/10d) or SoC arms evaluated separately, and all arms combined. This difference was significant for AEs and SAEs for all arms combined after covariate adjustment (Table 2). Table 1. Table 2. Conclusion: In moderate COVID-19 patients, concomitant HQN may delay recovery on RDV and showed no impact on recovery with SoC alone. The AE profile of HQN pos patients was worse than that observed for HQN neg patients, regardless of RDV treatment. Disclosures: Jose Ramon Arribas, MD, Alexa (Advisor or Review Panel member, Speaker's Bureau, Other Financial or Material Support, Personal fees)Gilead Sciences Inc. (Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau, Other Financial or Material Support, Personal fees)Janssen (Advisor or Review Panel member, Speaker's Bureau, Other Financial or Material Support, Personal fees)Merck (Advisor or Review Panel member, Speaker's Bureau, Other Financial or Material Support, Personal fees)Viiv Healthcare (Advisor or Review Panel member, Speaker's Bureau, Other Financial or Material Support, Personal fees) Jose Ramon Arribas, MD, NO DISCLOSURE DATA Arun J. Sanyal, MD, AbbVie (Consultant)Akarna (Shareholder)Amarin (Consultant)Ardelyx (Consultant)Astra Zeneca (Consultant, Research Grant or Support)Boehringer (Consultant)Bristol Myers Squibb (Research Grant or Support)Conatus (Consultant)Cumberland (Research Grant or Support)Durect (Shareholder)Elsevier (Other Financial or Material Support, Royalties)Exhalenz (Shareholder)Fibrogen (Consultant)Genfit (Shareholder)Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator, Research Grant or Support)Haemoshear (Shareholder)Indalo (Shareholder)Intercept (Research Grant or Support)Jannsen (Consultant)Lilly (Consultant)Malinckrodt (Research Grant or Support)Merck (Research Grant or Support)Nimbus (Consultant)Nitto Denko (Consultant)Novartis (Consultant)Pfizer (Consultant)Salix (Consultant)Sanyal Biotechnology (Employee, Shareholder, Other Financial or Material Support, President)Shire (Research Grant or Support)Takeda (Consultant)Tiziana (Shareholder)Tobira (Consultant)UptoDate (Other Financial or Material Support, Royalties)Zafgen (Consultant) Bum Sik Chin, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Bum Sik Chin, MD, NO DISCLOSURE DATA Shirin Kalimuddin, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Stefan Schreiber, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Emon Elboudwarej, PhD, Gilead Sciences Inc. (Employee, Shareholder) Yuan Tian, PhD, Gilead Sciences Inc. (Employee, Shareholder) Robert H. Hyland, MD, Gilead Sciences Inc. (Employee, Shareholder) Devi SenGupta, MD, Gilead Sciences Inc. (Employee, Shareholder) Anand Chokkalingam, PhD, Gilead Sciences (Employee) Anu Osinusi, MD, Gilead Sciences (Employee) Diana M. Brainard, MD, Gilead Sciences (Employee) Christoph Lübbert, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Chien Boon Lye, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Chien Boon Lye, MD, NO DISCLOSURE DATA Judith A. Aberg, MD, Theratechnology (Consultant) Enrique Navas Elorza, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Karen T. Tashima, MD, Bristol-Myers Squibb (Research Grant or Support)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator)GlaxoSmithKline (Research Grant or Support)Merck (Research Grant or Support)Tibotec (Research Grant or Support)Viiv Healthcare (Research Grant or Support) Mark McPhail, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)